Effect of Urate-Lowering Therapy on the Progression of Kidney Function in Patients With Asymptomatic Hyperuricemia: A Systematic Review and Meta-Analysis - Lin Zhang; Kang An; Xingyu Mou; Mei Zhang; Qiaoli Su; Shuangqing Li (Frontiers Media S.A., 2022)
Background: Hyperuricemia is involved in the risk of chronic kidney disease (CKD). However, whether urate-lowering therapy (ULT) can influence the progression of kidney function in patients with asymptomatic hyperuricemia is still controversial. We conducted a systematic review and meta-analysis to evaluate the effect of ULT on the progression of kidney function in asymptomatic hyperuricemia patients.Methods: The MEDLINE, EMBASE and Cochrane databases were searched without language, national or ethnic restrictions for randomized controlled trials published prior to November 30, 2020, that compared ULT with controlled therapy in patients with asymptomatic hyperuricemia.Results: Eleven studies were included for qualitative synthesis. ULT did not ameliorate eGFR slopes (WMD 0.36 ml/min/1.73 m2 per year, 95% CI: −0.31, 1.04), or lead to reductions in kidney events (RR 1.26; 95% CI: 0.80, 2.00) or all-cause mortality (RR 1.00; 95% CI: 0.65, 1.55), although ULT resulted in a decrease in serum uric acid levels (WMD −2.73 mg/dl; 95% CI: −3.18, −2.28) and lowered the incidence of gout episodes (0.9 vs 2.7%, RR 0.38; 95% CI: 0.17, 0.86).Conclusion: In patients with asymptomatic hyperuricemia, ULT did not decay the progression of kidney function. Long-term and larger sample studies are needed to verify the results.Systematic Review Registration: [www.crd.york.ac.uk/PROSPERO/#recordDetails], identifier [CRD42020204482].